Cyclophosphamide-induced myeloid-derived suppressor cell population is immunosuppressive but not identical to myeloid-derived suppressor cells induced by growing TC-1 tumors - Mikyšková, Romana; Indrová, Marie; Polláková, Veronika; Bieblová, Jana; Símová, Jana; Reiniš, Milan (Journal of immunotherapy, 2012)
Myeloid-derived suppressor cells (MDSC) play an important role in tumor escape from antitumor immunity. MDSC accumulate in the lymphoid organs and blood during tumor growth and their mobilization was also reported after cyclophosphamide (CY) administration. In this communication, spleen MDSC accumulating after CY therapy (CY-MDSC) were compared with those expanded in mice bearing human papilloma viruses 16-associated TC-1 carcinoma (TU-MDSC). Although both CY-MDSC and TU-MDSC accelerated growth of TC-1 tumors in vivo, their phenotype and immunosuppressive function differed. CY-MDSC consisted of higher percentage of monocyte-like subpopulation and this was accompanied by lower relative expression of immunosuppressive genes and lower suppression of T-cell proliferation. After interferon-γ stimulation, the expression of immunosuppressive genes increased, but the suppressive ability of CY-MDSC did not reach that of TU-MDSC. The phenotype and function of MDSC obtained from mice bearing TC-1 tumors treated with CY was, in general, found to lie between CY-MDSC and TU-MDSC. After in vitro cultivation of MDSC in the presence of interleukin 12 (IL-12), the percentage of CD11b+/Gr-1+ cells decreased and was accompanied by an increase in the percentage of CD86+/MHCII+ cells. The strongest modulatory effect was noticed in the group of CY-MDSC. The susceptibility of CY-MDSC to all-trans-retinoic acid (ATRA) was also evaluated. In vitro cultivation with ATRA resulted in MDSC differentiation, and ATRA inhibited MDSC accumulation induced by CY administration. Our findings identified differences between CY-MDSC and TU-MDSC and supported the rationale for utilization of ATRA or IL-12 to alter MDSC accumulation after CY chemotherapy with the aim to improve its antitumor effect.
Keywords: interferon gama; protinádorové látky; buněčná diferenciace; myši; Animals; CD11b Antigen; Tretinoin; regulace genové exprese u nádorů; Lymphocyte Activation; mužské pohlaví; cyklofosfamid; tretinoin; Humans; Interferon-gamma; Spleen; Cell Differentiation; Myeloid Cells; Human papillomavirus 16; antigeny CD11b; experimentální nádory; proliferace buněk; lidský papilomavirus 16; myši inbrední C57BL; lidé; Cell Line, Tumor; Cyclophosphamide; Mice; zvířata; interleukin-12; myeloidní buňky; aktivace lymfocytů; slezina; T-lymfocyty; Mice, Inbred C57BL; Antineoplastic Agents; Neoplasm Transplantation; Gene Expression Regulation, Neoplastic; T-Lymphocytes; antigeny CD86; B7-2 Antigen; Cell Proliferation; Interleukin-12; Male; transplantace nádorů; Neoplasms, Experimental; nádorové buněčné linie